Multisystem inflammatory syndrome in children (MIS-C) and “Near MIS-C”: A continuum? - Khafaja, Sarah; Youssef, Nour; El Zein, Zeinab; Boutros, Celina F.; Bou Karroum, Samer; Abdel-Halim, Nour; Salameh, Rim; Hodroj, Daniella; El Meski, Nour; Nasrallah, Oussama; Bidikian, Aram; Bou Saba, Ghassan; et al. (Frontiers in Pediatrics, 2023)
Introduction: Reports of multisystem inflammatory syndrome in children (MIS-C), following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, have been increasing worldwide, with an incidence varying significantly across studies based on the definition used for the diagnosis. At our tertiary medical center in Lebanon, we encountered several cases that presented a diagnostic challenge because they mimicked MIS-C but did not meet the US Centers for Disease Control and Prevention (CDC) definition. We decided to review these cases and describe their features in comparison with cases that met the CDC criteria of MIS-C and those that had an alternative diagnosis. Methods: This is a retrospective chart review of subjects aged <19 years old admitted to the American University of Beirut Medical Center (AUBMC) between March 1st, 2020, and May 31st, 2021, with suspected or confirmed MIS-C, following documented COVID-19 infection, with sufficient or insufficient criteria for diagnosis. Subjects were classified into 3 groups: “MIS-C”, “Near MIS-C” and “Alternative Diagnosis”. Results: A total number of 29 subjects were included in our cohort. Fever was present in all subjects. In the MIS-C group, evidence for cardiovascular system involvement was the most common feature followed by the mucocutaneous and gastrointestinal systems. In the “Near MIS-C” and “Alternative Diagnosis” group, gastrointestinal symptoms were the most common with only one patient with cardiac abnormalities and none with coagulopathy. Subjects with typical MIS-C presentation had higher inflammatory markers when compared to subjects in the other groups. Almost all the subjects had positive IgG for SARS-CoV-2. Of the 29 subjects, the Royal College of Paediatrics and Child Health (RCPCH) case definition would have identified all suspected cases without an alternative diagnosis as MIS-C, whereas the World Health Organization (WHO) and the CDC definitions would have excluded 6 and 10 subjects, respectively. Conclusion: MIS-C presents a diagnostic challenge due to the nonspecific symptoms, lack of pathognomonic findings, and potentially fatal complications. More research is needed to fully understand its pathogenesis, clinical presentation spectrum, and diagnostic criteria. Based on our experience, we favor the hypothesis that MIS-C has a continuum of severity that necessitates revisiting and unifying the current definitions.